PENGARUH AKUNTANSI MANAJEMEN, KUALITAS INFORMASI, EFISIENSI BIAYA DAN KETEPATAN WAKTU TERHADAP KINERJA KEUANGAN PT.SURYA SUKSES - Elok Kurniawati (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2018)
In economic unstable conditions, the company is required to take advantage of existing capabilities as much as possible in order to maximum and tough competition,the company should have good management and identify the problems and selecting and implies a process manager, to improve performance to the maximum. Activity-based management includes two dimensions of the costs of providing cost information about resource activity products, customers, suppliers and distribution channels. Activity-based costing is useful to improve accuracy of charges. Dimension process of providing information about what to do why it should be carried out how an activity should be implemented in order to reduce costs. This research aims to demonstrate the effect of the use of accounting information management is focused on the frequency of publication of regular reports, the frequency of the publication of the report update and quality management accounting information as well as the personality of the manager of financial performance on PT.Surya Success. The population used in this study is the manager PT.Surya Success. This data used is secondary data types. This study is based on a quantitative approach to the techniques of multiple linear regression analysis with SPSS. According to the research done can be seen that the quality of information didn’t significantly affect financial performance, Management Accounting, Cost Efficiency, Timeliness real impact on financial performance.